New Cytotoxic Sesquiterpenoids from Siegesbeckia glabrescens - Qian Wu; Hua Li; So Yoon Lee; Hwa Jin Lee; Jae-Ha Ryu (Molecules, 2015)
Two new sesquiterpenoids, siegenolides A (1) and B (2), and two known sesquiterpenes 3 and 4 were isolated from Siegesbeckia glabrescens. Their structures were elucidated by spectroscopic analyses, and they were further evaluated for their cytotoxic activities against human cancer cells (MCF-7, AsPC-1, SW480, HCT 116, HepG2, HeLa). Compounds 1–4 showed differential cytotoxic effects on the target cancer cells with IC50 values in the range of 0.9–33.3 μM.